'More reputation than she deserves': remembering suffrage in Wyoming. Issue 1 (2nd January 2017) - Morris, Katy
Abstract: As the first territory and state where women voted in the U.S., and in fact the first place in the world where women exercised full enfranchisement, Wyoming's past should raise pressing questions about the history of women's suffrage. However, scholars typically explain the unusual event as a political hoax, a joke, or an effort to increase the population of the fledgling territory. At the heart of the scholarly treatment of Wyoming suffrage lies the controversial figure of Esther Hobart Morris. Upheld as the 'mother of woman suffrage' in local lore, and viewed as a false heroine by most historians, Morris embodies the contradictions of western suffrage. In this essay, I reinsert Morris into the history of suffrage in Wyoming and analyze how Wyomingites remember and commemorate the story of Morris from the 1890s to the 1970s. By taking the symbolic role of Esther Morris seriously, I argue that suffrage in Wyoming mattered, not only to the women who exercised the vote but also to the collective identity of Wyomingites. I suggest that the conflation of Esther Morris with the Wyoming pioneer ultimately created a radical space of possibility for western women throughout the twentieth century. I show how Esther Morris provided a critical example of independent, western femininity that Wyoming women have since mobilized to demand their rights and fashion their own forms of transgressive womanhood.